Features and critical issues of process innovations - Giorgio Giallocosta (Agathón)
‘Process’ innovations – inclusive (but not substitutive) of similar ‘product’ evolutions (and further factors with which unravel activities of architecture’s production and management) – represent as many ‘countermeasures’ to the challenges posed by the current ‘complexity’s’ that characterize the construction industry. Some features, background and critical issues are outlined.